Polypyrrole actuators: the effects of polymer thickness and voltage scan rate on fractional charging and isotonic actuation strain. Issue 1 (15th October 2018) - Zheng, Wen; Whitten, Philip G; Spinks, Geoffrey M
Abstract: For conducting polymer actuators to be practically useful, they need to be able to generate large forces and displacements and respond quickly. The simplest way to generate larger forces is to produce thicker actuators, but this approach has a negative impact on the response time. The effects of polypyrrole film thickness and voltage scan rate on the electrochemical actuation strain rate are investigated in this study. The rate of oxidative charging is shown to follow a standard Fickian diffusion model suggesting that the migration of ions into the polymer from the electrolyte is the dominant rate-determining mechanism. The migration rate is slow with full oxidation requiring several minutes for film thicknesses of just 10 μ m. The free strains generated were found to be directly proportional to the oxidative charge passed. The isotonic actuation strains were additionally reduced by increasing applied stress and this effect was attributed to the increase in Young's modulus that occurs during polypyrrole oxidation. A simple model is presented that predicts the change in modulus during oxidation and gives reasonable estimates of the isotonic actuation for PPy actuators of different thickness and when subjected to different stresses.